Jabez Upham correspondence - Upham, Jabez, 1764-1811.
ALS written by Upham to fellow Massachusetts politician William Stedman chiefly reflecting Upham's state of mind.
U.S. representative from Massachusetts and lawyer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Stedman, William, -- 1765-1831 -- Correspondence; Massachusetts -- Politics and government -- 1775-1865.; Lawyers; Representatives, U.S. Congress -- Massachusetts